(untitled) (Biological Sciences - PJSIR, 2000)
Disease response of plants in terms of induced browning and phytoalexin (induced secondary metabolites) production were recorded in the tissues of Cicerarietinum (Chick pea) treated with the High Molecular Weight Crude Elicitor Preparations, HMWCEP "Polysaccharides" of Hypnea musciformis (red algae), Padina tetrastromatica (brown algae) and Ulva lactulus (green algae). A UV-visible spectrophotometric method has been developed for the quantification of induced secondary metabolites with time.